Can Acupuncture Treatment of Hypertension Improve Brain Health? A Mini Review - Sun, Jongjoo; Ashley, John; Kellawan, J. Mikhail (Frontiers in Aging Neuroscience, 2019)
With age, cerebrovascular and neurodegenerative diseases (e.g., dementia and Alzheimer’s) are some of the leading causes of death in the United States. Related to these outcomes is the increased prevalence of hypertension, which independently increases the development of cerebrovascular and neurodegenerative diseases. While a direct mechanistic link between hypertension and poor brain health is unknown, many hypothesize that the etiology stems from poor blood pressure (BP) and cerebrovascular regulation. This dysfunction fosters hypoperfusion of the brain, causing stress to the tissue through a nutrient mismatch, subtly damaging the brain over many years. Current Western medical treatment relies on pharmacological treatment (mainly beta-blockers, angiotensin-converting enzyme inhibitors, or a combination of the two). However, Western treatments have not been successful in mitigating brain health outcomes and are burdened with unwanted side effects and non-adherence issues. Alternatively, traditional East Asia medicine has used acupuncture as a treatment for hypertension and may offer a promising approach in response to the limitations of conventional therapy. While detailed clinical and mechanistic experimental evidence is lacking, acupuncture has been observed to reduce BP and improve endothelial function in hypertensive adults. Further, acupuncture has been shown to have specific cerebrovascular effects, increasing cerebrovascular reactivity in healthy adults, highlighting possible neuroprotective properties. Therefore, our review is aimed at evaluating acupuncture as a treatment for hypertension and the potential impact on brain health. We will interrogate the current literature as well as discuss the proposed neural and vascular mechanisms by which acupuncture acts.